2011
DOI: 10.3727/096368910x557191
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Two- and Three-Dimensional Cell Culture on the Chondrogenic Potential of Human Adipose-Derived Mesenchymal Stem Cells after Subcutaneous Transplantation with an Injectable Hydrogel

Abstract: Articular cartilage is an avascular tissue composed of chondrocytes, a unique cell type responsible for abundant matrix synthesis and maintenance. When damaged, it never heals spontaneously under physiological circumstances. Therefore, the delivery of mesenchymal stem cells using hydrogel has been considered for cartilage repair. This study aims at investigating the influence of in vitro chondrogenic differentiation of human adipose tissue-derived stem cells (hATSCs) on in vivo cartilage formation when associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 56 publications
(78 reference statements)
1
82
0
Order By: Relevance
“…27,28 Besides, it is reported that the expression of chondrogenic markers increased when grown in three-dimensional (3D) structure compared to monolayer. 29 Type I collagen is another component of collagen fibril in discs. The result of RT-PCR showed similar expression between the control and pre-differentiated ADSCs, partially consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Besides, it is reported that the expression of chondrogenic markers increased when grown in three-dimensional (3D) structure compared to monolayer. 29 Type I collagen is another component of collagen fibril in discs. The result of RT-PCR showed similar expression between the control and pre-differentiated ADSCs, partially consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The media were renewed three times a week. Chondrogenic differentiation was evaluated at day 35 by staining of glycosaminoglycans with Alcian blue (SigmaeAldrich) (Dominici et al, 2006) while the expression of Aggrecan (ACAN) was assessed by real time PCR (Merceron et al, 2011).…”
Section: Chondrogenic Differentiationmentioning
confidence: 99%
“…While some experiments are reported in the form of visual snapshots and qualitative comparisons [14,15], others provide more detailed cell density estimates [2,5]. A even more detailed approach is to report the precise numbers and location of individual cells [3].…”
Section: Introductionmentioning
confidence: 98%